Hymecromone Administration in Real Clinical Practice: Results of the Prospective Multicentre Observational Study in the Republic of Kazakhstan - A. V. Nersesov; D. A. Kaybullaeva; V. S. Rakhmetova; I. A. Lozinskaya; A. K. Kurmangalieva; V. S. Ayupova; A. B. Orazbaeva; A. K. Kanabaeva; Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Introduction. This multicentre prospective non-interventional observational study was conducted to obtain additional data about Odeston efficacy and safety in routine clinical practice. The objectives of the study included collection of clinical characteristics of patients, evaluation of Odeston effects in treatment of biliary pain and changes in the gallbladder emptying, evaluation of compliance to therapy, and treatment effect satisfaction.Materials and methods. The study was conducted from July 2020 to April 2021 at the premises of 60 study sites in 4 cities of the Republic of Kazakhstan. Patients having indications for Odeston administration according to the patient leaflet were enrolled. The study included 2 patient visits and an intermediate telephone contact. A visual analogue scale and RAPID questionnaire were used to characterise biliary pain; severity of associated symptoms, bowel habit and a quality of life according the SF-12 were also assessed. A rate of a ≥50 % reduction in symptom severity was used as a primary efficacy criterion; a rate of a ≥10 improvement in the SF-12 quality of life score was used as a secondary efficacy criterion. Compliance to treatment was evaluated using a number of days on Odeston. Treatment satisfaction was assessed using 5 grades.Results. 877 patients, 68.2 % of females and 31.8 % of males, were included in the study; the mean age was 46.0 ± 14.9 years. Primary functional biliary disorder was diagnosed in 65.3 % of patients, chronic non-calculous cholecystitis — 51.4 %, uncomplicated gallbladder disease — in 8.9 %, biliary sludge — 38.4 %, sphincter of Oddi functional disorder — 5.3 % of patients. A dose of Odeston was prescribed at the discretion of the physician. Group A patients received 600 mg (n = 89), group B received 1200 mg of Odeston a day (n = 788). In group B, an incidence of pronounced pain interference with daily living activities was higher. In both groups, the mean VAS scores were reduced to 1 point on treatment, a primary efficacy criterion was achieved in 77.3 % of patients in group A and in 79.8 % of patients in group B, р < 0.05. In both groups, a reduction in the incidence of constipation and diarrhea (р < 0,001) and an increase in the mean scores of physical and mental functioning were noted (р < 0.001, though a secondary efficacy criterion was not achieved (a ≥10 change in the SF-12 score). A prevalence of ultrasonographic sings of biliary sludge was reduced, and an increased gallbladder emptying was observed (p < 0.001). 77.4 % of patients in a total group of patients reported about drug administration for 21 days. A number of patients who were completely satisfied with treatment was higher in group B (p = 0.027).Conclusions. It was found that biliary pain interfered with daily living activities and commonly accompanied by other symptoms of gastrointestinal dysmotility. Odeston effectively reduces the severity of biliary pain, corrects dyspeptic disorders and normalizes stool pattern in patients with functional and organic diseases of the biliary system. Treatment satisfaction was higher with a dose of 1200 mg a day, particularly in more pronounced interference of pain with daily living activities.